2017
DOI: 10.7567/jjap.56.101001
|View full text |Cite
|
Sign up to set email alerts
|

Current linearity and operation stability in Al2O3-gate AlGaN/GaN MOS high electron mobility transistors

Abstract: To investigate current linearity and operation stability of metal-oxide-semiconductor (MOS) AlGaN/GaN high electron mobility transistors (HEMTs), we have fabricated and characterized the Al2O3-gate MOS-HEMTs without and with a bias annealing in air at 300 degrees C. Compared with the as-fabricated (unannealed) MOS HEMTs, the bias-annealed devices showed improved linearity of I-D-V-G curves even in the forward bias regime, resulting in increased maximum drain current. Lower subthreshold slope was also observed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(46 citation statements)
references
References 74 publications
(92 reference statements)
1
45
0
Order By: Relevance
“…We carried out a simulation to reproduce the C-V curve on a computer using a simulator developed previously by K. Nishiguchi 21,35) . In our previous work 18) , we assumed a Dit distribution and a reduction in carrier concentration to fit the experimental curve without assuming a bulk deep level.…”
Section: Simulation Results To Find Dominant Levelsmentioning
confidence: 99%
“…We carried out a simulation to reproduce the C-V curve on a computer using a simulator developed previously by K. Nishiguchi 21,35) . In our previous work 18) , we assumed a Dit distribution and a reduction in carrier concentration to fit the experimental curve without assuming a bulk deep level.…”
Section: Simulation Results To Find Dominant Levelsmentioning
confidence: 99%
“…To investigate the properties of the detected discrete level, the C-V curve was simulated using a simulator developed previously 40,41) . First of all, the possibility that the observed electric properties of the Mg-ion-implanted sample were dominated by the interface states should be examined.…”
Section: Simulation Of C-v Curvementioning
confidence: 99%
“…5(b). Several groups have reported that the gate controllability of AlGaN/GaN MIS-gate HEMTs enhances by reducing the interface-state density after some post-annealing processes after oxide layer deposition [15][16][17][18]. To improve the electrical properties of MIS-gate HEMTs, we carried out the post metallization annealing (PMA) process [19].…”
Section: Electrical Properties Of Recessed-gate Algan/gan Hemts Prmentioning
confidence: 99%